2009
DOI: 10.1590/s1678-77572009000500019
|View full text |Cite
|
Sign up to set email alerts
|

Abrasion wear resistance of different artificial teeth opposed to metal and composite antagonists

Abstract: One of the most important properties of artificial teeth is the abrasion wear resistance, which is determinant in the maintenance of the rehabilitation's occlusal pattern.Objectives:This in vitro study aims to evaluate the abrasion wear resistance of 7 brands of artificial teeth opposed to two types of antagonists.Material and methods:Seven groups were prepared with 12 specimens each (BIOLUX – BL, TRILUX – TR, BLUE DENT – BD, BIOCLER – BC, POSTARIS – PO, ORTHOSIT – OR, GNATHOSTAR – GN), opposed to metallic (M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 17 publications
1
20
0
2
Order By: Relevance
“…40 The antagonist material is a major consideration in the choice of the artificial teeth to be used in the prosthesis. 41 The results from the current clinical study indicate that the status of the opposing dentition does not confer additional risk of fracture or wear of the reconstruction. The results from an extensive literature review of commonly used restorative materials and their effects on the opposing dentition showed that the extent and rate of wear are influenced by many intraoral factors, including the restorative material.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…40 The antagonist material is a major consideration in the choice of the artificial teeth to be used in the prosthesis. 41 The results from the current clinical study indicate that the status of the opposing dentition does not confer additional risk of fracture or wear of the reconstruction. The results from an extensive literature review of commonly used restorative materials and their effects on the opposing dentition showed that the extent and rate of wear are influenced by many intraoral factors, including the restorative material.…”
Section: Discussionmentioning
confidence: 59%
“…A definite connection between wear resistance and the chemical composition of the dental teeth materials could not be found 40 . The antagonist material is a major consideration in the choice of the artificial teeth to be used in the prosthesis 41 . The results from the current clinical study indicate that the status of the opposing dentition does not confer additional risk of fracture or wear of the reconstruction.…”
Section: Discussionmentioning
confidence: 71%
“…Dental rehabilitation for this group of individuals may include direct or indirect restorations, depending on the severity of the case . The performance of indirect dental restorations used in prosthetic rehabilitation treatment is of great clinical interest, because degradation of the restorative material may produce some drawbacks, especially those related to changes in the occlusal vertical dimension, leading to several consequences, such as craniofacial disorders, reduced chewing efficiency, fatigue of the masticatory muscles, discomfort, and even impairment of the esthetics . For instance, laboratory‐processed resin nanoceramics are one of the materials considered for the rehabilitation of these patients; these nanoceramics are a new generation of indirect resin composites that contain a high density of inorganic ceramic fillers and poly‐functional methacrylate monomers .…”
mentioning
confidence: 99%
“…Higher stability and performance can be achieved by adding organic filler components that may be simply cross-linked or even highly cross-linked. Major improvements in wear performance [8][9][10][11] or hardness, for example, can be achieved by applying inorganic filler components as done in restorative or veneering composites, and already partially in resin teeth. The modification of the chemical formulation is a tightrope walk, because increased strength and hardness may go hand in hand with increased toughness.…”
Section: Introductionmentioning
confidence: 99%